Temperature Effects During a Sublethal Chronic Metal Mixture Exposure on Common Carp (Cyprinus carpio) - Castaldo, Giovanni; Pillet, Marion; Ameryckx, Leen; Bervoets, Lieven; Town, Raewyn M.; Blust, Ronny; De Boeck, Gudrun (Frontiers in Physiology, 2021)
The aquatic environment is the final sink of various pollutants including metals, which can pose a threat for aquatic organisms. Waterborne metal mixture toxicity might be influenced by environmental parameters such as the temperature. In the present study, common carp were exposed for 27 days to a ternary metal mixture of Cu, Zn and Cd at two different temperatures, 10 and 20 ºC. The exposure concentrations represent 10% of the 96 h-LC50 (concentration lethal for the 50% of the population in 96 h) for each metal (nominal metal concentrations of Cu: 0.08 µM; Cd: 0.03 µM and Zn: 3 µM). Metal bioaccumulation and toxicity as well as changes in the gene expression of enzymes responsible for ionoregulation and induction of defensive responses were investigated. Furthermore the hepatosomatic index and condition factor were measured as crude indication of overall health and energy reserves. The obtained results showed a rapid Cu and Cd increase in the gills at both temperatures. Cadmium accumulation was higher at 20 °C compared to 10 ºC, whereas Cu and Zn accumulation was not, suggesting that at 20 ºC, fish had more efficient depuration processes for Cu and Zn. Electrolyte (Ca, Mg, Na and K) levels were analyzed in different tissues (gills, liver, brain, muscle ) and in the remaining carcasses. However no major electrolyte losses were observed. The toxic effect of the trace metal ion mixture on major ion uptake mechanisms may have been compensated by ion uptake from the food. Finally, the metal exposure triggered the upregulation of the metallothionein gene in the gills as defensive response for the organism. These results, show the ability of common carp to cope with these metal levels, at least under the condition used in this experiment.